THE INFLUENCE OF EMOTIONAL INTELLIGENCE, ORGANIZATIONAL CITIZENSHIP BEHAVIOR, MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE - Herman Afandi; Ufi Rumefi (Politeknik Ubaya, 2025)
Observations of the leadership and various employees at the Pasuruan Regency Education and Culture Office indicate that employee performance remains suboptimal, primarily due to insufficient emotional intelligence, which hampers their ability to manage personal emotions and interact effectively with others. This deficiency adversely affects their thoughts and actions. Additionally, there is a notable lack of Organizational Citizenship Behavior (OCB), characterized by employees' reluctance to assist colleagues with incomplete tasks and limited interaction among peers, which complicates the provision of advice when encountering work-related issues. From the performance assessment survey results indicate that employee initiative and cooperation are considered lacking. This can lead to suboptimal work performance, which will have an impact on the company's sustainability. Therefore, this study was conducted to further discuss this issue. Furthermore, employees exhibit a preference for solitary work and display dissatisfaction when required to engage in teamwork. Moreover, the absence of incentive from both superiors and colleagues results in employees neglecting their respective responsibilities and failing to assist one another. The work atmosphere is detrimental due to loudness and lack of cleanliness, resulting in decreased employee comfort and ultimately diminishing performance.This study's results revealed a substantial simultaneous impact on Employee Performance (Y). Furthermore, there exists a partial significant effect of Emotional Intelligence, organizational citizenship, and work environment variables on employee performance. The motivation variable is recognized as having no meaningful influence.